Explaining Protest in the Aftermath of the Great Recession in Europe: The Relevance of Different Economic Indicators - Francesca Vassallo (Coordinamento SIBA, 2016)
The European economic crisis has brought economic hardship and prolonged instability to many countries in the European Union. While economies are struggling to recover, citizens have opted to become more vocal unconventionally. Mass protest, public occupations and demonstrations have dominated Europe. Yet, numbers of people choosing to protest need to be assessed to verify whether the economic recession is indeed responsible for a surge in protest activism on the continent. With the use of multiple rounds from the European Social Survey (2006-2012), this article tests the hypothesis linking unconventional political behavior in Europe to the economy. Findings suggest that overall European protest levels are not higher after the crisis, although confrontational activism has spiked in few countries. Economic variables retain instead an important role in the explanation of protest in the post-recession era, with both objective and subjective economic measures supporting a grievance theory explanation of why Europeans protest. Economic decline matters in the selection of protest as a mode of political participation.